Exploring the role of management in the implementation of talent management - Ndou, Mathildah Mashudu; Mofokeng, Jacob Tseko; Khosa, Dorcas (Technium Social Sciences Journal, 2021)
The South African public sector institutions are faced with the challenges of proper implementation of talent management. The aim of this research is to explore the role of management in the implementation of talent management within the Department of Public Works, Roads and Infrastructure in the Limpopo Province. The inability by management to properly show their role in the management and implementation of talent management at all levels in the public sector has brought poor performance of duties by employees due to lack of motivation and low morale. A qualitative research approach was used. Purposive sampling was adopted using semi-structured interviews to gather data from participants. The findings revealed that challenges like career development, skills development, motivation, succession planning and remuneration packages including benefits allowances were the main limits which mainly prevented proper implementation of talent management in the Department.